Long Period Vs Short Period in Situ Drain in Paraumbilical Hernia Repair - Muhmood Hussain, Saad (Diyala Journal of Medicine, 2019)
Background:Paraumbilical Hernia is more likely to be incarcerated or strangulated so the repair of such hernia is advisable as early as possible. Objective: To outcome the benefit of the long period that the drain had been kept in situ after Paraumbilical Hernia repair for reducing the complications. Patients and Methods:150 patients were included in this study which had been perform in Diyala province in the period of January 2004 – December 2006 to whom mayo's repair had been performed for their Paraumbilical Hernia and these patient had been divided in to tow groups, group(1) which include 75 patients in whom the drain had been left for 48 hours only, group(2) include 75 patients in whom the drain had been left for 7 days. Results:We found that in the group (1), 30 (40%) patients had develop seroma collections and 16 (21.33%) patients had developed wound infection with this seroma, 10 (13.33%) patients developed hematoma collections and 7 (9.33%) developed wound infection with this hematoma. In group (2) we found that only 7 (9.33%) patients developed seroma collection and 3 (4%) patients developed wound infection with this seroma, 3 (4%) patients developed hematoma collection and 2 (2.66%) patients developed wound infection with this hematoma.